Building Muslim Costumer Loyality in Marketplace Through MDA Framework For Male and Female Millenials - Kusumadewi, Rita; Perwiranegara, Agus Alamsyah; Aini, Farihatu (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose: Gamification have been widely applied as marketing strategies for sustainable valueadded development. This research have explored the relationships between the gamification components and consumer continuous usage at marketplace’s games.Design/methodology: This research analyzed and comparing behaviour between man and woman, how game elements anda mechanics impact their gaming behavior and awaken positive feelings to increase the stickiness of the marketplace. This research model empirically surveyed 100 (each man and woman) marketplace app users, based on the Mechanics–Dynamics–Aesthetics (MDA) framework.Findings: The results show that the self-challenge is a pre-factor that affects self-benefit, fun, and social interaction, while self-benefit and social interaction affect fun. The results also show that both men and women, they all feel that the games on the marketplace have simple playing rules, making it fun for players to play and win. The results of the hypothesis test show that (1) The MDA Framework variable partially has a positive and significant influence on the Loyalty variable for male game players in the marketplace by 25.71%, and (2) partially has a positive and significant influence on the variable Loyalty of female game players in the marketplace by 26.01%.Practical implications: The empirical implication of this research is to determine the conditions and factors that cause man and woman become a loyal customer of a marketplace.Originality/Value: It's not just the education or entertainment industry that must involve games in its activities, but marketplaces can also build consumer loyalty through games. The contribution of this research focuses on efforts focus on fun activities that can build customer loyalty of the market place